Effect of reception an dig efficacy on spike performance an manner of execution in volleyball - Palao, J. M.; Santos, J. A.; Urena, A. (Journal of Human Movement Studies, 2006)
The cyclic and sequential characteristic of the Volleyball garne causes actions to be related to each other in terms of the manner of execution and performance. The present paper studies the effect of previous actions (reception-dig) on spike performance and the manner the spike is executed (type of spike, zone and direction). A total of 4968 actions from 33 male matches and 2450 actions from 23 female matches in the 2000 Olympic Garnes were analysed. The results show that performance of reception and dig conditioned the spike performance and its manner of execution. Also, teams tend to accelerate the game, when reception and dig so allow, to reduce the Opponent team's time to organise their defense.